Sistem Pendukung Keputusan Pemilihan Pengrajin Ulos Ragi Hotang Terbaik Di Desa Meat Menerapkan Metode Maut - Irvan Siahaan (Bulletin of Artificial Intelligence, 2023)
Meat Village is a center for making hotang yeast ulos which is carried out by women. The Meat Village Office selects the best yeast hotang ulos craftsmen every year to improve the community's economy and provide enthusiasm for hotang yeast ulos craftsmen who aim to improve the quality of hotang yeast ulos which has criteria for neatness, motifs, and color combinations. The problem faced by the Meat Village office is still using the manual method, especially in determining the best hotang yeast ulos craftsmen in Meat Village. On this occasion the author proposes the selection of hotang yeast ulos craftsmen using a decision support system using the MAUT Method, programming in Microsoft Visual Studio 2010 with Visual Basic language and MySQL as a database. From the results of my research I want to help the Meat Village office in determining the best hotang yeast ulos craftsmen in Meat Village by using a Decision Support System using the multi attribute utility theory (MAUT) method. Those who got the best score in selecting hotang yeast ulos craftsmen were A8 on behalf of Ester Simanjuntak with a score of 0.427 as the first rank, A9 with the name Oni Siahaan the value of 0.363 in the second rank and A4 with the name Herbeslina Maharaja the value of 0.344 in the third rank.